Effect of formulation parameters on Sumatriptan succinate Buccal Mucoadhesive Tablet: Quality by Design approach - Wable Arti J, Thokal Seema B, Mittal Sandeep S, Shirsat Ajinath E, Bhingare Chandrashekhar L, Ingle Pramod L (Journal of Applied Pharmaceutical Science, 2014)
The present investigation was focused on application of QbD approach to see the effect of formulation variables on buccal mucoadhesive tablets containing anti migraine drug, Sumatriptan succinate to circumvent the first pass effect and to provide sustained release. Risk assessment of critical material and process parameters are linked to critical quality attributes (CQAs) of the product with respect to obtain total quality product profile (TQPP). The effect of critical parameters (polymer: drug ratio, carbopol: HPMC E5 ratio and diluent quantity) were investigated by executing design of experimentation (DoE) using Box-Behnken statistical model. DR10 hr (drug release after 10 hrs), mucoadhesive strength and mucoadhesion time were considered critical quality attributes (CQAs). Sumatriptan succinate buccal mucoadhesive (SBM) tablets were prepared by direct compression method and were evaluated as per pharmacopoeia procedure. Multiple regression analysis and ANOVA were employed to identify and estimate the effect of important parameters and establish their relationship with CQAs and to obtain design space for optimization purpose. The best in-vitro drug release profile, mucoadhesive strength, mucoadhesion time and desired product quality was achieved with the formulation prepared in the region of design space. FDS graph, 3D response graph and Overlay plot were successfully implemented to interpret effects and selection of significant parameters on CQAs. Hence, it can be concluded that formulation parameters affects the SBM tablet and can be successfully optimized using the QbD a novel approach resulting into the SBM tablets which could provide sustained effect and avoid first pass effect.
Keywords: Sumatriptan succinate, Mucoadhesive buccal tablet, Carbopol 971P, 3D response, QbD, Design Space.